Bambara groundnut starch-soluble dietary fibre nanocomposite stabilised emulsions: Optimisation of emulsion stability and studies on time-dependent rheological properties - Yvonne Maphosa; Oladayo Adeyi; Daniel Imwansi Ikhu-Omoregbe; Victoria A. Jideani (South African Journal of Chemical Engineering)
Due to their inherent thermodynamic instability, emulsions require stabilisers to maintain their integrity and prevent destabilisation. The effect of emulsion components (Bambara groundnut starch-soluble dietary fibre nanocomposite (STASOL), orange oil and water) on the rheological and stability properties of STASOL-stabilised emulsions was optimised. A randomised d-optimal exchange mixture design was used to determine the ratio of STASOL, orange oil and water required for a stable emulsion. The stability of these emulsions was evaluated using the initial mean backscattering index (BSAVO), Turbiscan stability index (TSI) and hysteresis loop area (HLA). The BSAVO (%), TSI and HLA of the emulsions ranged from 50.73 % (14:30:56 STASOL:oil:water) to 70.47 % (20:30:50 STASOL:oil:water), 0.0005 (20:30:50 STASOL:oil:water) to 0.1000 (8:42:50 STASOL:oil:water) and 0.37 Pas-1 (10:32:58 STASOL:oil:water) to 5.69 Pas-1 (20:30:50 STASOL:oil:water), respectively. Emulsions exhibited a direct relationship between STASOL concentration and stability metrics, with the highest stability achieved at 20 % STASOL concentration, 30 % orange oil and 50 % water. An increase in STASOL concentration coupled with a decrease in oil concentration results in a stable emulsion. Numerical optimisation and experimental validation confirmed the effectiveness of the selected formulation, demonstrating STASOL's potential as a natural stabiliser in beverage emulsions and its ability to enhance stability compared to synthetic alternatives.